Mediating effects of shopping orientations and moderating effects of gender on relationships between personal factors and repatronage behavioural intention - Wong, Yue Teng (2014)
Personal-centric marketing is determined by, and therefore an indicator of, the repatronage behavioural intention. The main objective of this study was to examine the factors related to repatronage behavioural intention among apparel adult shoppers. The Theory of Planned Behaviour and 3M Model of Motivation and Personality functioned as the basis for the theoretical framework of the study. A conceptual framework was developed from the theoretical settings to identify the personal factor influences of i) elemental traits (openness to experience, conscientiousness, extraversion, agreeableness, neuroticism and material needs); ii) compound traits (need for activity and impulsiveness) and iii) situational traits (shopping confidence and interpersonal influence susceptibility) on repatronage behavioural intention. The study also investigated the mediating effects of shopping orientations (utilitarian shopping orientation and hedonic shopping orientation) in the relationships between Npersonal factors and repatronage behavioural intention. The moderating effect of gender was examined in the study so as to ascertain the gender differences with regard to the influences of personal factors on repatronage behavioural intention. The conceptualized model in the study was then developed into shopper typologies. A quota sampling was used to gather the data of 600 adult apparel shoppers from five shopping malls, namely, Berjaya Time Square, The Mines, Sunway Pyramid, Mid Valley Megamall and 1 Utama located in the Klang Valley in Malaysia. The selfadministered questionnaire was distributed using the store-intercept technique. There were 569 useable responses maintained for the analysis of the study. The data were statistically analyzed using descriptive analysis, Pearson Product Moment Correlation, Structural Equation Modeling and hierarchical and non-hierarchical cluster analysis. It was observed that a moderate to high level of repatronage behavioural intention was identified among the Malaysian apparel adult shoppers. A relatively good fit of the model to the data was obtained in the study. There were significant linear relationships found between the traits of agreeableness, material needs, need for activity and interpersonal influence susceptibility and repatronage behavioural intention. The hedonic shopping orientation was distinguished as a mediator in the relationships between neuroticism, material needs, impulsiveness and repatronage behavioural intention. The hedonic mediating structural model showed the advancement of 59% to the direct model (46%) to explain the variance in repatronage behavioural intention. However, the utilitarian shopping orientation was not a mediator in the relationships between personal factors and repatronage behavioural intention. Moderation effect of gender showed that although male and female shoppers did not share the same regression weights in the hypothesized model, the predictors of repatronage behavioural intention functioned similarly for the two shopper groups. Based on the confirmed hypothesized model, shopper typologies of Self-confined, Apathetic Shoppers; Moderate, Pragmatic Shoppers and Confident, Enthusiastic Shoppers were constructed. This study appeared to supportthe importance of personal-centric elements, with the empirically substantiated findings alongside the theoretical rationalizations, in understanding the repatronage behavioural intention of apparel adult shoppers. This study has highlighted some implications and made recommendations to facilitate the repatronage behavioural ntention of the shoppers. The necessity for future research on the repatronage behavioural intention is also highlighted.